Cosmological Visions, Multispecies Practices, and Planetary Health in Pandemic Times - Judith Schlehe (UNHI PRESS, 2022)
The cosmovisions of the so-called world religions are based on assumed divides between nature and culture, nonhuman and human, man and God, and these divisions have long been reproduced by the social sciences. Only recently, a radical interrelatedness has been thematized and acknowledged by certain scholars, and indeed, the current pandemic reminds us of zoonoses and the manifold relationships that humans have with other forms of life. At the same time, local or folk religions offer alternative ontologies including transgressions between humans and animals or spirits. Thus, they indicate that there is no “above” or “outside of” nature. Perhaps future multispecies practices will be shaped by a new awareness of such relatedness and symbiosis, as offered by the Planetary Health approach: a relational health concept that will prepare for future challenges by focusing on the interrelationships between human health, political, economic, and social contexts as well as the biodiversity of our planet.